Protection of Trade Secrets in the Context of Indonesian Law and the TRIPS Agreement: Perlindungan Hukum terhadap Rahasia Dagang ditinjau dari Aspek Hukum Indonesia dan TRIPS Agreement - Imaduddin, Muhammad; Rato, Dominikus; Anggono, Bayu Dwi (Universitas Muhammadiyah Sidoarjo, 2023)
This research explores the legal framework governing trade secret protection in Indonesia, aligning with international standards set by the TRIPS Agreement of the WTO. Utilizing normative legal research and legislative analysis, the study evaluates the effectiveness of Law No. 30 of 2000 on Trade Secrets in providing crucial legal safeguards for economically valuable confidential information. The dispute resolution process for trade secret violations in Indonesia involves legal steps such as violation identification, evidence collection, mediation, arbitration, and civil proceedings, culminating in court decisions determining compensation and, if necessary, criminal penalties. The study finds that Indonesia's trade secret laws significantly impact innovation, trade, and investment, playing a vital role in international dispute resolution and providing robust rights to trade secret owners. Highlights: The study evaluates the effectiveness of Indonesia's Law No. 30 of 2000 in aligning with international standards for trade secret protection, specifically those outlined in the TRIPS Agreement of the WTO. The research outlines the comprehensive dispute resolution process in Indonesia for trade secret violations, encompassing identification, evidence collection, and legal proceedings, with court decisions determining compensatory measures and potential criminal penalties. Findings underscore the substantial impact of trade secret protection on fostering innovation, facilitating trade, and attracting investments in Indonesia, while playing a pivotal role in international dispute resolution mechanisms. Keywords: Trade Secrets, Legal Protection, Indonesia, TRIPS Agreement, Innovation